Dispersion Modeling of Gas Emissions and TSP with AERMOD at Coal-Fired Power Plant in East Java and Evaluation of Health Risks Assessment - Bestita, Nasyrah Shader; Dewi, Kania (Syntax Literate, 2025)
Coal-fired power plants (CFPPs) have significant negative environmental impacts due to emissions from non-fugitive sources like stacks. This research aims to predict the concentration, dispersion patterns, and health risks of pollutants emitted from these plants, focusing on SO₂, NOₓ, and TSP using the AERMOD model. Meteorological and terrain data were processed through AERMET and AERMAP. Results indicate that pollutants mainly disperse to the east and south, with peak concentrations 1.5 to 2 km south of the source. SO₂ concentrations reached 15,121.18 µg/m³ (1-hour), 5,740.66 µg/m³ (24-hour), and 287.67 µg/m³ (annual), exceeding regulatory limits. NOₓ peaked at 15,589.02 µg/m³ (1-hour), 5,782.41 µg/m³ (24-hour), and 288.48 µg/m³ (annual), also surpassing limits. TSP concentrations peaked at 330.30 µg/m³, exceeding the 24-hour limit. Model validation showed good accuracy for SO₂ but overestimated NOₓ and underestimated TSP. Health risk assessments identified 23 high-risk locations for SO₂ and one for NOₓ during 24-hour exposure, while TSP posed no significant risk. Recommendations include improving model accuracy by incorporating fugitive sources and chemical transformation modules to enhance air quality management in complex terrains.